ANALISIS IMPLEMENTASI FATWA DSN-MUI PENERAPAN INKLUSI KEUANGAN SYARIAH PADA PEMBIAYAAN MURABAHAH UNTUK PENINGKATAN KESEJAHTERAAN NASABAH DI BPRS - Hafid, Ekaradiah; Bunyamin, Andi; Lawang, Hasanna; Raehana, Syarifa; Arsyad, Yusri Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of Islamic financial inclusion principles in murabahah financing at BPRS Bobato, Tidore Islands City, and to examine the implementation of DSN-MUI Fatwa Number 04/DSN-MUI/IV/2000 concerning murabahah contracts in such financing practices. The main focus of this study is to determine the extent to which Islamic financial inclusion through murabahah products is able to provide broader financial access to the community, especially MSMEs, in order to improve their economic welfare in a sustainable manner. The research method used is qualitative research with a case study approach. Data collection was carried out through observation techniques, in-depth interviews, and documentation. Research informants consisted of the management of BPRS Bobato, especially the Marketing Manager, as well as active customers who use murabahah financing. The data obtained were then analyzed descriptively to provide a comprehensive picture of the implementation of Islamic financial inclusion and the conformity of murabahah practices with the DSN-MUI fatwa. The results of the study indicate that the implementation of Islamic financial inclusion at BPRS Bobato has been running well, especially in expanding access to financial services for people who previously had difficulty reaching conventional banking. The implementation of DSN-MUI Fatwa No. 04/2000 has also been in accordance with sharia principles, as evidenced by price and margin transparency. However, challenges remain, including low customer understanding and the need for strengthened internal oversight.